Cryopreserved peripheral blood cells functioning as autografts in patients with chronic granulocytic leukaemia in transformation. Issue 6174 (19th May 1979) - Goldman, J M; Catovsky, D; Hows, J; Spiers, A S; Galton, D A
Abstract : Six patients with chronic granulocytic leukaemia (CGL) in transformation were treated with cytotoxic drugs or cytotoxic drugs plus total body irradiation, followed by infusion of reconstituted autologous peripheral blood cells that had been collected from them at diagnosis and stored in liquid nitrogen for up to 58 months. In four cases the blood and bone-marrow appearances were rapidly restored to those of typical chronic-phase disease. In three of these patients transformation recurred at 74, 32, and 26 weeks respectively. One patient was still in second chronic phase at eight weeks. One of the patients who entered a second transformation was restored to a third chronic phase by further treatment with cytotoxic drugs and a second autograft. Cryopreserved autologous blood cells may thus restore some patients with CGL in transformation to chronic-phase disease and so may help to prolong life.